PENGARUH MANAJEMEN RISIKO PERBANKAN SECARA FINANSIAL TERHADAP KINERJA KEUANGAN PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - Adi Irawan; Maulana Hadi Kusuma (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
This research was conducted to examine the influence of credit risk (NPL), liquidity risk (LDR), operational risk (BOPO) on financial performance (ROA) at conventional commercial banks listed on the Indonesia Stock Exchange in 2015-2019, either partially or simultaneously. The analytical tool used in this research is panel data regression. Based on the results of the analysis and discussion that has been done, it can be concluded that partially the NPL variable does not have a significant influence on financial performance (ROA), the LDR variable does not have a significant influence on financial performance (ROA). BOPO variable has a significant influence on financial performance (ROA). Simultaneous testing of credit risk (NPL), liquidity risk (LDR) and operational risk (BOPO) influences financial performance (ROA). The result of the coefficient of determination test shows that the percentage of the influence of the independent variable on the dependent variable is 71.2%%, while the remaining 28.8% is influenced by other variables such as market risk and others which are not included in this study.